Boron nitride nanotube clusters and their hybrid nanofibers with polycaprolacton: Thermo-pH sensitive drug delivery functional materials. (15th March 2020) - Pour Khalili, Nazila; Moradi, Rasoul; Kavehpour, Pirouz; Islamzada, Faiq
Graphical abstract: Highlights: BNNTs nano-clusters were synthesized and examined for drug encapsulation purposes. BNNTs/PCL hybrid nanofiber mats were synthesize and characterized using simultaneous electrospinning-electrospraying. Thermo-pH responsively and senility of produced functional polymeric and hybrid materials were analyzed. Successful encapsulation of doxorubicin anti-cancer drug was performed inBNNTs nanoclusters and BNNTs/PCL nanofibers. Controlled release examination results illustrate that Dox@BNNTs/PCL mats exhibit superior release trends. Abstract: Electrospinning-electrospraying is a promising technique in synthesis of hybrid polymeric materials for many applications, especially for drug delivery purposes. Since one of the most worrisome adverse effects of anticancer drugs such as doxorubicin (Dox), cisplatin and Fluorouracil (5FU) is cardiotoxicity, finding a possible novel strategy to prevent or manage this lethal side effect should be considered as one of the most important issues for investigation. In this study, we fabricated a fibrous scaffold containing encapsulated Dox to prevent Dox-induced cardiomyopathy with limited clinical use and improve clinical outcomes of chemotherapy in cancer patients. Simultaneous electrospinning-electrospraying was used to produce hybrid nanofibers intended to be used for controlled releases of doxorubicin. Boron nitride nanotubes (BNNTs) clusters were synthesized and employed for encapsulation of Dox and then they were subjected to electrospraying. Electrospinning of polycaprolactone (PCL) solution was performed simultaneously to provide a nanofiber network substrate for BNNT/Dox nanocapsules. Polycaprolactone nanofibers with average diameters at the range of 240 ± 55–450 ± 50 nm were synthesized depending on various electrospinning conditions. BNNTs/Dox homogenous solution in methanol/acetone (50/50 V/V) was prepared and electrosprayed on the surface of the nanofibers. Different properties of the produced electrospun mats such as morphology, thermal characteristics and in vitro drug releases were investigated. The results revealed the excellent thermo-pH sensitivity of the prepared BNNTs/PCL functional nano-mats.